Much Ado about Nothing? Do Domestic Firms Really Benefit from Foreign Direct Investment? - Görg, Holger; Greenaway, David (World Bank, 2013)
Governments the world over offer significant inducements to attract investment, motivated by the expectation of spillover benefits to augment the primary benefits of a boost to national income from new investment. There are several possible sources of induced spillovers from foreign direct investment. This article evaluates the empirical evidence on productivity, wage, and export spillovers in developing, developed, and transition economies. Although theory can identify a range of possible spillover channels, robust empirical support for positive spillovers is at best mixed. The article explores the reasons and concludes with a review of policy aspects.